Multi-level porous carbon prepared via a facile sugar-blowing method for high-performance lithium-sulfur batteries. (27th July 2019) - Su, Wenxiao; Feng, Wangjun; Cao, Yue; Li, Miaomiao; Song, Changkun; Cheng, Lingjin
Abstract: A novel 3D multi-level porous carbon is obtained via a simple facile sugar-blowing method. The multi-level porous carbon sreves as the sulfur host and prepares multi-level porous carbon/sulfur cathode, which exhibited high initial discharge capacity of 1200 mAh g −1 at 0.1 C. After 200 cycles at 0.2 C, the multi-level porous carbon/sulfur cathode remained retentive capacity of 80%. These excellent electrochemical performance can be attributed to the abundant interconnected multi-level porous carbon, providing spacious channels for the transportation of electrons and lithium ions. In addition, multi-level porous carbon prevent the shuttling of polysulfides in charge and discharge process.